Teaching compassionate care to nursing students in a digital learning and teaching environment. Issue 3 (June 2018) - Hofmeyer, Anne; Toffoli, Luisa; Vernon, Rachael; Taylor, Ruth; Klopper, Hester C.; Coetzee, Siedine Knobloch; Fontaine, Dorrie
Abstract: Background: Healthcare that is technically excellent, but without compassion, fails to meet the expectations of patients. Ample evidence about teaching compassion to nursing students in classrooms exists; however, few studies report online teaching. Aim: This study explored final year nursing students' perceptions of compassion and practising compassion before and after studying an online compassion module. Methods: An exploratory, descriptive qualitative approach guided data collection and analysis. Students responded to open-ended questions before and after studying the module. Findings: Themes derived from the analysis: being present, acting to relieve suffering, getting the basics right, going forward . Being present for patients was evident in statements such as placing yourself in their shoes, taking time to listen carefully and doing things that mattered (e.g., using touch to convey compassion). Acting compassionately depends on communicating to understand the suffering of others and what matters. Being resilient involved getting the basics right (e.g., positive self-care and lifestyle practices, cultivating supportive networks, setting boundaries). Going forward included being mindful to act compassionately as new registered nurses and supporting colleagues. Conclusions: This study provided new insights into how students' new knowledge translated into compassionate action. Students described the positive impact of small acts of compassion from one nurse to another that enhanced teamwork and resilience. Recognising the critical role of compassion to patient and family outcomes, provider wellbeing, and organisational culture, these findings could be used by nurse leaders and educators to develop evidence-informed curricula to foster the practice of compassion which all nurses aspire to provide.